QUALITATIVE ANALYSIS OF NATIONAL AND INTERNATIONAL ETHNOGRAPHIC PUBLICATIONS IN MANAGEMENT AND ORGANIZATIONAL STUDIES - Yen-Tsang, Chen (2013)
The purpose of this paper is to investigate ethnography’s intellectual evolution in the fields of management and organizational studies, for the period 1995 to 2011, by analyzing citations and co-citations in international publications, and in national ones from 2000 to now. As it is not possible to employ the same citation and co-citation analysis technique for the national publications, a contextual analysis of the stage Ethnography is found in Brazil was opted for. The methodology used in the research was a documentary analysis of the stage of ethnography in international and national publications. It was noted that for international studies, the ethnographic work of Geertz (1973), Van Maanen (1988) and Clifford and Marcus (1986) made important contributions, thus greatly influencing subsequent research. This research has shown that these authors, as regards the central theme, had greater proximity to it and formed its main group. Major changes were also observed in relation to the central cluster for the period examined regarding international journals. At the national level, it can be affirmed that ethnographic studies still has low popularity among academics in administration, possibly due to that the fact it requires long periods of time from the data collection, through analysis and until final publication.